2022
DOI: 10.1111/petr.14377
|View full text |Cite
|
Sign up to set email alerts
|

Successful use of intra‐operative continuous renal replacement therapy in pediatric liver transplant recipients: Single center case series

Abstract: Background Acute kidney injury (AKI) is common in pediatric patients undergoing liver transplantation (LT), with an incidence 17%–55%. Fluid, metabolic, and acid–base aberrancies are often pronounced pre‐operatively and further worsened by events during LT, making intra‐operative continuous renal replacement therapy (CRRT) an option for critically ill LT recipients. Methods All pediatric LT performed at our institution who underwent intra‐operative CRRT between January 2017 and August 2021 were included. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…Blanchette et al. were the first to our knowledge to report successful use of iCRRT in nine patients 20 . This study, first in pediatric LT, demonstrated feasibility and safety of iCRRT.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…Blanchette et al. were the first to our knowledge to report successful use of iCRRT in nine patients 20 . This study, first in pediatric LT, demonstrated feasibility and safety of iCRRT.…”
Section: Discussionsupporting
confidence: 53%
“…Blanchette et al were the first to our knowledge to report successful use of iCRRT in nine patients. 20 This study, first in pediatric LT, demonstrated feasibility and safety of iCRRT. Recipients in this study requiring iCRRT were more likely to have acute liver failure, had a significantly longer post-transplant intensive care unit length of stay in comparison to the rest of the cohort, with no significant differences in reoperations, hospital length of stay, or recipient or graft survival.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations